Comparison of Roche and Lumipulse quantitative SARS-CoV-2 antigen test performance using automated systems for the diagnosis of COVID-19. (July 2021) - Hirotsu, Yosuke; Sugiura, Hiroki; Maejima, Makoto; Hayakawa, Miyoko; Mochizuki, Hitoshi; Tsutsui, Toshiharu; Kakizaki, Yumiko; Miyashita, Yoshihiro; Omata, Masao
Highlights: We compared the results of quantitative SARS-CoV-2 Ag tests of Roche and Lumipulse. Both Ag tests were positive for samples containing high viral loads. Quantitative Ag levels correlated with viral loads and threshold cycle values. Quantitative Ag levels determined using the two Ag tests were highly correlated. The two Ag tests showed high concordance up to 9 days after symptom onset. Abstract: Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) continues to spread worldwide. Here, we evaluated the performance of two quantitative antigen (Ag) tests, the Roche and Lumipulse Ag tests, using automated platforms. Methods: We collected 637 nasopharyngeal swab samples from 274 individuals. Samples were subjected to quantitative reverse transcription PCR (RT-qPCR), the Roche Ag test and Lumipulse Ag test. Results: When RT-qPCR was used as a reference, the overall concordance rate of the Roche Ag test was 77.1% (491/637) with 70.0% (341/487) sensitivity and 100% specificity (150/150). When inconclusive results of the Lumipulse Ag test were excluded, the overall concordance rate of the Lumipulse Ag test was 88.3% (467/529) with 84.8% (330/389) sensitivity and 97.9% (137/140) specificity. The overall concordance rate between the Roche and Lumipulse Ag tests was 97.9% (518/529) with 96.7% (322/333) sensitivity and 100% (196/196) specificity. Quantitative Ag levels determined using the Roche and Lumipulse Ag tests were highly correlated (R 2 = 0.922). The Roche and Lumipulse Ag tests showed high concordance up to nine days after symptom onset, with progressively lower concordance after that. Conclusions: The Roche and Lumipulse Ag tests showed equivalent assay performance and represent promising approaches for diagnosing coronavirus disease 2019.